Lessons from New Zealand’s COVID-19 outbreak response (2020)
In the absence of a vaccine for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), or of highly effective pharmaceutical treatments for COVID-19, countries have implemented a large range of nonpharmaceutical interventions to control the spread of the virus.1 These interventions differ in their level of stringency (ie, the severity of the measures) and their ultimate objective (eg, prevent health systems being overwhelmed, suppress incidence to low levels, or reduce incidence to zero and keep it there). With many countries facing epidemic resurgence, evaluating the impact of different strategies implemented in the early phases of the pandemic is crucial for developing an effective long-term response